Antibiotic therapy for pelvic inflammatory disease - Savaris, Ricardo F (Cochrane Database Syst Rev, 2017)
BACKGROUND: Pelvic inflammatory disease (PID) is an infection that affects 4% to 12% of young women, and is one of the most common causes of morbidity in this age group. The main intervention for acute PID is the use of broad‐spectrum antibiotics which cover Chlamydia trachomatis, Neisseria gonorrhoeae, and anaerobic bacteria, administered intravenously, intramuscularly, or orally. In this review, we assessed the optimal treatment regimen for PID. OBJECTIVES: To assess the effectiveness and safety of antibiotic regimens used to treat pelvic inflammatory disease. SEARCH METHODS: We searched the Cochrane Sexually Transmitted Infections Review Group's Specialized Register, which included randomized controlled trials (RCTs) from 1944 to 2016, located through electronic searching and handsearching; the Cochrane Central Register of Controlled Trials (CENTRAL), Ovid platform (1991 to July 2016); MEDLINE (1946 to July 2016); Embase (1947 to July 2016); LILACS, iAHx interface (1982 to July 2016); World Health Organization International Clinical Trials Registry Platform (July 2016); Web of Science (2001 to July 2016); OpenGrey (1990, 1992, 1995, 1996, and 1997); and abstracts in selected publications. SELECTION CRITERIA: We included RCTs comparing the use of antibiotics with placebo or other antibiotics for the treatment of PID in women of reproductive age, either as inpatient or outpatient treatment. We limited our review to comparison of drugs in current use that are recommended for consideration by the 2015 US Centers for Disease Control and Prevention (CDC) guidelines for treatment of PID. DATA COLLECTION AND ANALYSIS: At least two review authors independently selected trials for inclusion, extracted data, and assessed risk of bias. We contacted investigators to obtain missing information. We resolved disagreements by consensus or by consulting a fourth review author if necessary. We assessed the quality of the evidence using GRADE criteria, classifying it as high, moderate, low, or very low. We calculated Mantel‐Haenszel risk ratios (RR), using either random‐effects or fixed‐effect models and number needed to treat for an additional beneficial outcome or for an additional harmful outcome, with their 95% confidence interval (CI), to measure the effect of the treatments. We conducted sensitivity analyses limited to studies at low risk of bias, for comparisons where such studies were available. MAIN RESULTS: We included 37 RCTs (6348 women). The quality of the evidence ranged from very low to high, the main limitations being serious risk of bias (due to poor reporting of study methods and lack of blinding), serious inconsistency, and serious imprecision. Azithromycin versus doxycycline There was no clear evidence of a difference between the two drugs in rates of cure for mild‐moderate PID (RR 1.18, 95% CI 0.89 to 1.55, I(2) = 72%, 2 RCTs, 243 women, very low‐quality evidence), severe PID (RR 1.00, 95% CI 0.96 to 1.05, 1 RCT, 309 women, low‐quality evidence), or adverse effects leading to discontinuation of treatment (RR 0.71, 95% CI 0.38 to 1.34, 3 RCTs, 552 women, I(2) = 0%, low‐quality evidence). In a sensitivity analysis limited to a single study at low risk of bias, azithromycin was superior to doxycycline in achieving cure in mild‐moderate PID (RR 1.35, 95% CI 1.10 to 1.67, 133 women, moderate‐quality evidence). Quinolone versus cephalosporin There was no clear evidence of a difference between the two drugs in rates of cure for mild‐moderate PID (RR 1.04, 95% CI 0.98 to 1.10, 3 RCTs, 459 women, I(2) = 5%, low‐quality evidence), severe PID (RR 1.06, 95% CI 0.91 to 1.23, 2 RCTs, 313 women, I(2) = 7%, low‐quality evidence), or adverse effects leading to discontinuation of treatment (RR 2.24, 95% CI 0.52 to 9.72, 5 RCTs, 772 women, I(2) = 0%, very low‐quality evidence). Nitroimidazole versus no use of nitroimidazole There was no conclusive evidence of a difference between the nitroimidazoles (metronidazole) group and the group receiving other drugs with activity over anaerobes (e.g. amoxicillin‐clavulanate) in rates of cure for mild‐moderate PID (RR 1.01, 95% CI 0.93 to 1.10, 5 RCTs, 2427 women, I(2) = 60%, moderate‐quality evidence), severe PID (RR 0.96, 95% CI 0.92 to 1.01, 11 RCTs, 1383 women, I(2) = 0%, moderate‐quality evidence), or adverse effects leading to discontinuation of treatment (RR 1.00, 95% CI 0.63 to 1.59; participants = 3788; studies = 16; I(2) = 0% , low‐quality evidence). In a sensitivity analysis limited to studies at low risk of bias, findings did not differ substantially from the main analysis (RR 1.06, 95% CI 0.98 to 1.15, 2 RCTs, 1201 women, I(2) = 32%, high‐quality evidence). Clindamycin plus aminoglycoside versus quinolone There was no evidence of a difference between the two groups in rates of cure for mild‐moderate PID (RR 0.88, 95% CI 0.69 to 1.13, 1 RCT, 25 women, very low‐quality evidence), severe PID (RR 1.02, 95% CI 0.87 to 1.19, 2 studies, 151 women, I(2) = 0%, low‐quality evidence), or adverse effects leading to discontinuation of treatment (RR 0.21, 95% CI 0.02 to 1.72, 3 RCTs, 163 women, very low‐quality evidence). Clindamycin plus aminoglycoside versus cephalosporin There was no clear evidence of a difference between the two groups in rates of cure for mild‐moderate PID (RR 1.02, 95% CI 0.95 to 1.09, 2 RCTs, 150 women, I(2) = 0%, low‐quality evidence), severe PID (RR 1.00, 95% CI 0.95 to 1.06, 10 RCTs, 959 women, I(2) = 21%, moderate‐quality evidence), or adverse effects leading to discontinuation of treatment (RR 0.78, 95% CI 0.18 to 3.42, 10 RCTs, 1172 women, I(2) = 0%, very low‐quality evidence). AUTHORS' CONCLUSIONS: We found no conclusive evidence that one regimen of antibiotics was safer or more effective than any other for the cure of PID, and there was no clear evidence for the use of nitroimidazoles (metronidazole) compared to use of other drugs with activity over anaerobes. Moderate‐quality evidence from a single study at low risk of bias suggested that a macrolide (azithromycin) may be more effective than a tetracycline (doxycycline) for curing mild‐moderate PID. Our review considered only the drugs that are currently used and mentioned by the CDC.